Creditos Y Cobranza Del "Almacen Distbend - Morán Iza, Cristina Victoria (2018)
The companies that offer products in the market in several lines such as appliances in general, motorcycles and technological lines, which are intended to generate economic resources and that are managed by a single person who is known as manager owner or owner, are regulated by the internal revenue service and complying with the established in article 19 of the Organic Law of internal taxation and its regulation of application that indicates that taxpayers who have exceeded the limits established in the immediately preceding fiscal year of your income 15 basic fractions, costs or expenses 12 basic fractions or by their patrimony 9 basic fractions, they are obliged to keep accounting, be natural or legal persons. This type of businesses market their products in cash with promotions, discounts and a Credit that nowadays has become a tool used by the warehouses to promote their products in order to increase their sales. This mode is preferred by Ecuadorian families to meet their needs because it allows them to acquire a good and cancel it in monthly installments. This research project is developed in the company "DISTBEND" located in the city ​​of Babahoyo, is a sole proprietorship, obliged to keep accounting, which has as its main activity the commercialization of household appliances in general, motor vehicles, technological products and general retail items ie their products are sold at final consumer.